2023
DOI: 10.1101/2023.10.26.23297560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GGC expansion inZFHX3causes SCA4 and impairs autophagy

Karla P. Figueroa,
Caspar Gross,
Elena Buena Atienza
et al.

Abstract: Despite linkage to 16q in 1996, the mutation for spinocerebellar ataxia type 4 (SCA4), a late-onset sensory and cerebellar ataxia, escaped detection for 25 years. Using long- read PacBio-HiFi and ONT-Nanopre sequencing and bioinformatic analysis, we identified expansion of a GGC DNA repeat in a >85% GC-rich region in exon 10 of theZFHX3gene coding for poly-glycine (polyG). In a total of 15 nuclear families from Utah and 9 from Europe, the repeat was expanded to >40 repeats in SCA4 patients accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Rudaks et al 1 also cite two other groups for achieving similar findings independently of each other. 3,4 One of those works by Figueroa et al, 3 reported as a manuscript in medRxiv, expanded the clinical descriptions of the original Swedish-American family reported back in 1996 by Flanigan et al 5 However, before all these publications, on October 3, 2023, our group released a manuscript, also in medRxiv, describing three SCA4 families in Sweden, 6 which was not mentioned by Rudaks et al 1 Our group evidently discovered the genetic defect independently of other groups, which illustrates how refined techniques improve diagnostics and contribute to new discoveries. Our group devoted more than a decade working on SCA4, which was part of two theses from the Karolinska Institute.…”
mentioning
confidence: 99%
“…Rudaks et al 1 also cite two other groups for achieving similar findings independently of each other. 3,4 One of those works by Figueroa et al, 3 reported as a manuscript in medRxiv, expanded the clinical descriptions of the original Swedish-American family reported back in 1996 by Flanigan et al 5 However, before all these publications, on October 3, 2023, our group released a manuscript, also in medRxiv, describing three SCA4 families in Sweden, 6 which was not mentioned by Rudaks et al 1 Our group evidently discovered the genetic defect independently of other groups, which illustrates how refined techniques improve diagnostics and contribute to new discoveries. Our group devoted more than a decade working on SCA4, which was part of two theses from the Karolinska Institute.…”
mentioning
confidence: 99%